Perhitungan Rasio Keuangan sebagai Alat Penilaian Tingkat Kesehatan pada Koperasi Perbaikan Masyarakat Wanita (Permata) Kabupaten Kuningan - Unsriyani, Enci; Irawan, Arry (Indonesian Accounting Literacy Journal, 2024)
This research was conducted at the Women's Community Improvement Cooperative (Permata) Kuningan Regency. The research purpose is to determine the results of financial performance at Permata Cooperative. The research method is descriptive quantitative with data collection techniques using interviews and documentation. Data source used comes from Permata Cooperative's financial statements for 2016-2020. Based on the results for capital aspect, Permata Cooperative obtained total score of 10.50 points with predicate "Sufficiently Normal". For aspect of productive asset quality, obtained a total score of 24 points with predicate "Normal". For efficiency aspect, total score of 9 points was obtained with predicate "Normal". For liquidity aspect, it received the title "In Special Observation" with a score of 5 points in 2016-2019 and 3.75 points in 2020. Then for financial performance of Permata Cooperative, it obtained a score of 48.5 points for 2016-2019 and 47.25 points for 2020 with predicate "Sufficiently Healthy".